A new pathogen, Myxobolus holzerae (Myxosporea: Myxozoa) causing severe gill disease in an Indian major carp Labeo rohita in a cold water wetland, Punjab (India). (October 2017) - Gupta, Aditya; Kaur, Harpreet
Abstract: The Indian major carp, Labeo rohita Hamilton, 1822 is a tropical freshwater cyprinid fish native to inland waters in Asia. Herein, we describe a novel myxozoan forming plasmodia in the gill lamellae of L. rohita from Ranjit Sagar Wetland in Punjab, India. Myxospores were consistent with the genus Myxobolus, round to elliptical in valvular view, lemon shaped in side view with a characteristic protrusion at the anterior end and a round posterior end; length 7.65 ± 0.07 μm, width 4.62 ± 0.09 μm. There were two polar capsules of equal length, pear shaped, length of polar capsule 2.54 ± 0.05 μm, width 1.60 ± 0.02 μm, with 5–6 turns of the polar filament. The 890 bp 18S rDNA sequence was up to 97% similar to M. catlae from other cyprinid fishes in India. In having, unique myxospore morphology and 18S rDNA sequence, we propose Myxobolus holzerae as new to science. Graphical abstract: Image 1 Highlights: A new species Myxobolus holzerae infecting gills of Labeo rohita has been described on the basis of morphology, 18S rDNA sequences and analyzed phylogenetically. Histopathological studies showed interlamellar epithelial (LE2) type of plasmodia which caused deformation of whole of the infected gill lamellae, therefore maximum loss of respiratory surface. The present study also indicated a close resemblance among the members of the genus Myxobolus recorded from same geographical location, tissue and cyprinid host.